Growth Pattern Study of Slender Walking Catfish (Clarias nieuhofii) as Environmental Biology Indicator - Helentina Mariance Manullang; Khairul Khairul (Mangifera Edu, 2020)
Slender walking catfish (Clarias nieuhofii) is a consumption fish that has a fairly high economical value. Local market prices can reach IRD 50.000-70.000/kg. People love this fish because of the delicious taste of the meat, which very different from the aquaculture catfish. Until now the production relies only on natural catches and there have been no cultivation efforts. But in recent years these out catfish are increasingly difficult to find in nature. The conversion of land into plantation areas caused the loss of the fish's original habitat. Based on community information, the habitat of this fish is found in Pasir Putih Village, Silangkitang District, Labuhan Batu Selatan Regency, and Bandar Tinggi Village, Bilah Hulu District, Labuhanbatu Regency, Indonesia. Differences in habitat conditions are known to affect fish growth patterns, including C. nieuhofii. This research aims to determine the pattern of the growth of the slender walking catfish in these different habitat conditions. Exploratory methods were used in this research and observation stations were determined through purposive sampling. Fish sampling was done using a fishing rod. The samples of fish captured were measured by the total length and weight. The results of the research show that the pattern of fish growth in Pasir Putih Village is negative allometric (W = 0.6944, b = 0.2463 and R2 = 0.9468) and in Bandar Tinggi Village shows negative allometric (W = 10.207, b = - 129.56, and R2 = 0.9711).